2023
DOI: 10.1371/journal.pone.0289426
|View full text |Cite
|
Sign up to set email alerts
|

High risk of virologic failure among HIV-infected children and adolescents routinely followed-up in Littoral region of Cameroon

Patient Juste Mbébi Enoné,
Calixte Ida Penda,
Grâce Ngondi
et al.

Abstract: Virological response to antiretroviral therapy (ART) remains a challenge for HIV-infected children and adolescents due to non-optimization of pediatric ART for resource-limited settings. In this study, we aimed to investigate factors associated with virologic failure (VF) in HIV-infected-children and adolescents on ART in Cameroon. A prospective patient-based cohort study was conducted among HIV-infected children (0–9 years) and adolescents (10–19 years) followed-up between November 2018 and October 2019 in 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Of the included studies, 15 were cross‐sectional, 10 were cohort, five were nested studies in clinical trials and two were case‐control (Table 1). The majority (29/32) of the studies 10,22,23,25–43,45–47,49–52 used a viral load threshold of ≥1000 copies/mL to define VNS. Bhardwaj et al.…”
Section: Resultsmentioning
confidence: 99%
“…Of the included studies, 15 were cross‐sectional, 10 were cohort, five were nested studies in clinical trials and two were case‐control (Table 1). The majority (29/32) of the studies 10,22,23,25–43,45–47,49–52 used a viral load threshold of ≥1000 copies/mL to define VNS. Bhardwaj et al.…”
Section: Resultsmentioning
confidence: 99%
“… 15 It has been shown that difficulties experienced in achieving virological success during adolescence may impact reservoir size and clinical outcomes. 16 It is worth noting that despite the high burden of paediatric HIV-1 infection in SSA, there still persists a gap in data concerning the quantitative characterization of HIV-1 DNA in reservoirs, especially in the Central African sub-region which is known for its high genetic diversity of HIV-1. 17 , 18 Most of studies reporting data on the quantitative profile of HIV-1 reservoirs on the SSA paediatric populations were conducted in Southern African countries and were focusing on very early treated infants.…”
Section: Introductionmentioning
confidence: 99%